Comparative taxonomy and breeding behavior of five populations of betta pugnax group (osphronemidae) from Johor, Malaysia [QH1]. - Lim, Teow Yeong (2009)
Taksonomi dan kelakuan pembiakan kumpulan Betta pugnax berdasarkan lima populasi dari Johor, Malaysia telah dikaji.